THE USE OF REWARDS TO MOTIVATE YOUNG LEARNERS IN LEARNING ENGLISH: A Descriptive Study on a fifth grade of Elementary School in Bandung - Mardiningsari, Harum (2013)
Penelitian ini berjudul "The Use of Rewards to Motivate Young Learners in Learning English (A descriptive study on a fifth grade of Elementary School in Bandun)". Penelitian ini bertujuan untuk mencari tahu respon siswa ketika mendapat reward dari guru. Dan juga untuk mencari tahu reward apa yang diberikan guru selama kegiatan dikelas. Penelitian ini dilakukan di salah satu Sekolah Dasar Negeri di Bandung. Penelitian ini menggunakan metode deskriptif kualitatif dan melibatkan seorang guru Bahasa Inggris dan siswa kelas 5 di sekolah tersebut sebagai pokok penelitian. Observasi dan wawancara digunakan dalam penelitian ini untuk mendapatkan data yang sesuai dengan pertanyaan penelitian. Kemudian, data tersebut di analisis dengan metode adaptasi dari Miles dan Huberman (1994). Hasil dari penelitian ini adalah siswa sangat senang dan antusias dalam belajar Bahasa Inggris setelah guru memberikan reward berupa pujian daripada reward berupa barang. Kata Kunci: Rewards, motivasi, siswa This study entitled "The Use of Rewards to Motivate Young Learners in Learning English (A descriptive study on a fifth grade of Elementary School in Bandung)". The objective of this study was to find out the students' responses when getting the rewards. Besides, it was also aimed at finding out the rewards used by the teacher. The data were taken from one public school in Bandung. This study employed a descriptive design and involved an EFL teacher and fifth grade students in that school as the subjects. In order to gain the data, observation and interview were conducted. Then, the data were analyzed by the framework adapted from Miles & Huberman (1994). The findings revealed that the students were happy and enthusiastic in learning English after the teacher gave them the intangible reward rather than the tangible. Keywords: Rewards, motivation, young learners